Challenges of community-based forest management with local institutional differences between South Korea and Indonesia. Issue 8 (16th November 2020) - Purnomo, Eko Priyo; Ramdani, Rijal; Salsabila, Lubna; Choi, Jin-Wook
ABSTRACT: This article compares the implementation of community-based forest management (CBFM) practices between South Korea and Indonesia and discusses the political and legal basis of land and natural resources of the two countries. A triangulation method was used for data collection and analysis. As a result, this study developed a theory about successful community institution development on forest management and recommendations for policy at local and national government levels. The Indonesian Government can learn from the success of the Korean Government in implementing CBFM sustainability and articulate local institutions' strategies.